The influence of high performance work system, organizational culture on employee performance, a study in The Ministry of Education in Oman - Al Rawas, Nadaa Mansoor Amer Al Rawas (2014)
The need to enhance the performance of employees in the ministry of education in Oman has made the researcher to conduct this study. Specifically, the study focuses on the influence of high performance work system (HPWS) and organizational culture on the performance of employees in the ministry of education in Oman. A cross sectional study of questionnaire survey research design was conducted in this respect. Questionnaire data was generated from 162 employees and the questionnaire were distributed by hand. The findings from the testing of the hypotheses demonstrated that HPWS have significant positive relationship with employees performance except for the performance management system (PMS) which shows a negative relationship with employees performance. The culture of the organizational was also found to have a positive effect on the performance of employees in the ministry. On this note, the study recommends for the urgent need by the ministry to give serious consideration to the performance management system if they want to achieve better performance. In conclusion the present study presented the theoretical and practical implication in addition to the limitations of the study and suggestions for future study are included in this regard